Optimisasi Energi Terbarukan dalam Pembangkitan Energi Listrik Menuju Desa Mandiri Energi di Desa Margajaya - Arif Febriansyah Juwito; Tarcicius Haryono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
Abstract— The Self-Sufficient Energy Village (DME) is one of main program from goverment about the village ability to produce energy . This program has been launched in 2007 by the President of Indonesia, to enhance energy security in rural area in using local energy. The criteria of Self-Sufficient Energy Village is the village capability to produce at least 60% of the total amount of energy, using renewable energy. Geographically Margajaya Village has solar and microhydro resource which is very potential for development. Furthermore, Margajaya village also produces plantation commodities like palm oil, which every week produces waste like palm bunches, The waste of which is a very potential biomass. The optimization of renewable energy for electrical power generation has been designed using HOMER in Margajaya village, which have annual power peak is 65kW and daily energy consumtion of 415kWh/day. The result from simulation of Hybrid renewable system in HOMER that showed Hydro, Biomass and grid is the best economical solution over hydro-biomass-PV with battery, to design hybrid system with minimum total net present cost (NPC) and cost of electricity. The system can serve annual 100% of load in Margajaya and have surplus of electricity, and could sell to grid as much of 408.492 kWh/years. Economically the system have cost of electricity is US$-0,167/kWh.